Primary biliary cholangitis: molecular pathogenesis perspectives and therapeutic potential of natural products - Zhao, Yanling; Wei, Shizhang; Chen, Lisheng; Zhou, Xuelin; Ma, Xiao (Frontiers in Immunology, 2023)
Primary biliary cirrhosis (PBC) is a chronic cholestatic immune liver disease characterized by persistent cholestasis, interlobular bile duct damage, portal inflammation, liver fibrosis, eventual cirrhosis and death. Existing clinical and animal studies have made good progress in bile acid metabolism, intestinal flora disorders inflammatory response, bile duct cell damage, and autoimmune response mechanisms. However, the pathogenesis of PBC has not been clearly elucidated. To discuss the latest understanding of the pathological mechanism, treatment options, and drug discovery of PBC. We focus on the pathological mechanism and new drug research and development of PBC in clinical and laboratory in recent 20 years. Current clinical treatment mode and symptomatic drug support obviously cannot meet the urgent demand of PBC patients, especially for the patients who do not respond to the current treatment drugs. New treatment methods are urgently needed. Drug candidates targeting reported targets or signals of PBC are emerging, albeit with some success and some failure. Single-target drugs can not achieve ideal clinical efficacy. Multitarget drugs are the trend of future research and development of PBC drugs.